(untitled) (MAUSAM, 2024)
Complex tectonics in the Maluku Sea cause frequent earthquakes in the mainland of Maluku, especially North Maluku. During 2017-2021, 1099 earthquakes occurred in the North, with an average magnitude of 4.4. The current study aims to map the maximum ground acceleration, maximum ground velocity and earthquake intensity in the North Maluku region between 2017 and 2021 to find areas with high and low earthquake impact. The method used in this study was to calculate the PGA (Peak Ground Acceleration) value with PGV (Peak Ground Velocity). Earthquake intensity is calculated using the equation that relates PGA to MMI. The PGA value in theNorth Maluku region ranges from 18-20.3 gal. and PGV values range from 8.6 to 9.6 cm/s. The earthquake’s intensity was on the MMI III scale because several active faults in North Maluku cause earthquakes with a magnitude of 4-5 with a depth varying from 10-50 km. Finally, the result of this study is expected to provide important information about areas with a low or high risk of earthquake impacts in North Maluku.